KELOMPOK TROFIK PADA KOMUNITAS ARTHROPODA TAJUK DAN LANTAI HUTAN DI HUTAN GUNUNG TANGKUBANPARAHU-JAWA BARAT: ILUSTRASI DENGAN DIAGRAM TROFIK HIPOTETIK - Indah Trisnawati D.T.; Tati S. Subahar (The East Java Biological Society, 2011)
Research on grouping the arthropod of Mt. Tangkuban Parahu, West Java, ecologically based on functional role and feeding habits (herbivore, predator, parasitoid) was done. The research was carried out during September 2001 – Januari 2002 using Modified Window Traps. Identifi cation of the arthropod was done up to family and morphospecies level. Five orders of flying arthropod that is Diptera (2043 individuals), Coleoptera (768 individuals), Hymenoptera (331 individuals), Homoptera (284 individuals), and 2 orders of non-flying arthropod (Collembola, 444 individuals; Acarina, 252 individuals) was collected on Mixed Forest and Pine Forest. In Mixed Forest, samples was dominated by Coleoptera (27 family, 90 morphospecies, 774 individuals), Diptera (26 family, 80 morphospecies, 2027 individuals), Hymenoptera (21 family, 67 morphospecies, 330 individuals), Collembola (5 family, 12 morphospesies, 444 individuals). While, Pine Forest was dominated by Diptera (22 famili, 59 morfospesies, 575 individu), Hymenoptera (21 famili, 54 morfospesies, 153 individu), Coleoptera (17 family, 54 morphospecies, 187 individuals), Collembola (5 family, 12 morphospecies, 738 individuals). Herbivores, saprovores, predators and parasitoids, respectively, were dominant groups collected from the Mixed Forest, while, herbivores, predators, parasitoids and saprovores, respectively, were dominant groups from the Pine Forest. Connectance value (C) measurement from hypothetical trophic structure diagram was carried out to compare the strength of trophic structure interaction between the Mixed and Pine Forests. C value from the Mixed Forest was lower than that of the Pine Forest (0.13 vs 0.21), showing that interaction strength of trophic structure from the complex Mixed Forest was weaker than that of the Pine Forest. If disturbed, a more complex trophic structure have relatively recover more slowly, so that changes in forest floristic composition will affect the trophic groups of arthropods, which ultimately affects the stability of forest ecosystems. Conversion of Mixed Forests into production forests, such as Pine forests, could increase the potential vulnerability of habitat destruction.